استخدام اللغة الخاصة (Jargon) باللغة العربية لدى طلاب معهد دار الهجرة للبنين: تحليل الأشكال والمعاني والوظيفة الاجتماعية اللغوية - Sukkan Arya Putra; Akhmat Sodikin (STIT Darul Hijrah Martapura, 2026)
ABSTRACT This study examines the Principles of Developing the Arabic Language Curriculum, which include four main foundations: philosophical, psychological, social, and technological. These foundations serve as essential pillars in building a curriculum that is not only pedagogically effective but also relevant to Islamic values and the demands of the modern era. Using a library research method with a descriptive qualitative method, this study analyzes various scientific literatures, books, and academic journals to obtain a comprehensive understanding of the fundamental principles of Arabic language curriculum development. The findings indicate that the philosophical foundation provides the value direction and educational goals based on the Islamic worldview; the psychological foundation requires curriculum alignment with learners’ characteristics and needs; the social foundation emphasizes the importance of connecting Arabic language learning with social realities; while the technological foundation highlights the role of digital innovation in enriching learning experiences. With an integrated understanding of these four foundations, the Arabic language curriculum is expected to become an inspiring and adaptive learning medium capable of shaping a generation that excels in language, character, and technological literacy. Keyword: Arabic language curriculum, development, educational foundations.